1995
DOI: 10.1111/j.1348-0421.1995.tb02162.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Bile Acid 7‐Dehydroxylating Bacteria from Human Feces

Abstract: Methods for isolation of fecal 7α‐dehydroxylating bacteria are presented. A total of 219 strains were isolated from feces of healthy humans, and their ability to 7‐dehydroxylate cholic, chenodeoxycholic, and ursodeoxycholic acids were examined. Of all the isolates, 14 strains were found to be capable of eliminating the hydroxy group at C‐7α and/or C‐7β. All the isolates were strictly anaerobic, Gram‐positive rods. Thirteen isolates were non‐sporeforming bacteria showing certain saccharolytic properties with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 16 publications
2
34
0
Order By: Relevance
“…56,57 Bacteria capable of converting primary to secondary bile acids have been isolated from humans. [58][59][60] The rodent isolate required unidentified Bacteroides spp. in co-culture due to an unidentified syntrophy.…”
Section: Bile Acid 7a/7b-dehydroxylation By Intestinal Bacteriamentioning
confidence: 99%
“…56,57 Bacteria capable of converting primary to secondary bile acids have been isolated from humans. [58][59][60] The rodent isolate required unidentified Bacteroides spp. in co-culture due to an unidentified syntrophy.…”
Section: Bile Acid 7a/7b-dehydroxylation By Intestinal Bacteriamentioning
confidence: 99%
“…Many studies (Archer et al, 1982 ;Ferrari et al, 1977 ;Hayakawa & Hattori, 1970 ;Hirano et al, 1981 ;Stellwag & Hylemon, 1979 ;Takamine & Imamura, 1995 ;White et al, 1980) on faecal bacteria having 7α-dehydroxylating activity have been reported. In these reports, the multistep bile acid 7α-dehydroxylation pathway was studied in detail only for strain VPI 12708 (Baron et al, 1991 ;Coleman et al, 1987 ;Doerner et al, 1997 ;Franklund et al, 1993 ;Mallonee & Hylemon, 1996 ;Mallonee et al, 1990Mallonee et al, , 1992.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the genera Clostridium and Eubacterium are the predominant intestinal species exhibiting bile acid 7α-dehydroxylating activity (Archer et al, 1982 ;Ferrari et al, 1977 ;Hayakawa & Hattori, 1970 ;Hirano et al, 1981 ;Stellwag & Hylemon, 1979 ; Takamine & Imamura, 1995). The presence of this activity in the intestinal microflora results in 7α-dehydroxylation of cholic acid and chenodeoxycholic acid, yielding deoxycholic acid and lithocholic acid, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of laboratories have isolated bile acid 7a-dehydroxylating bacteria from fecal samples but it was not easy to isolate them because of their small population (13,14). The level of fecal bacteria capable of bile acid 7a-dehydroxylation in normal humans ranges from 10 2 to 10 5/g of wet weight feces (14).…”
mentioning
confidence: 99%